Genetic population structure of the Asian longhorned tick, Haemaphysalis longicornis, in Japan - Kiyohito Morii; Yoshiko Sakamoto; Yuya Watari; Hayato Iijima; Kandai Doi; Kaori Morishima; Hirotaka Komine; Kimiko Okabe; Koichi Goka (Experimental and Applied Acarology, 2025)

Combination of a membrane bioreactor with a rotating biological contactor holding several diverse metazoans can reduce excess sludge with fouling mitigation - Toru Miwa; Shimon Nagatsuma; Yuga Hirakata; Mami Nagai; Tomoya Ikarashi; Yuya Takimoto; Takahiro Watari; Takashi Yamaguchi; Masashi Hatamoto (Water Research, 2024)

Harnessing iron materials for enhanced decolorization of azo dye wastewater: A comprehensive review - Thu Huong Nguyen; Duc Viet Nguyen; Masashi Hatamoto; Yuya Takimoto; Takahiro Watari; Khac-Uan Do; Takashi Yamaguchi (Environmental Research, 2024)

Economic costs of invasive non-native species in urban areas: An underexplored financial drain - Gustavo Heringer; Romina D. Fernandez; Alok Bang; Marion Cordonnier; Ana Novoa; Bernd Lenzner; César Capinha; David Renault; David Roiz; Desika Moodley; Elena Tricarico; Kathrin Holenstein; et al. (Science of The Total Environment, 2024)

Sewage-derived substances and dead microbial cells cause gel biofilm formation in membrane bioreactors treating real sewage - Toru Miwa; Yuya Takimoto; Yujiro Tokuda; Takahiro Watari; Takashi Yamaguchi; Masashi Hatamoto (Chemical Engineering Journal, 2023)

Genetic relationships among populations of the small Indian mongoose (Urva auropunctata) introduced in Japan - Takuma Sato; Yuya Watari; Takamichi Jogahara (Mammal Research, 2023)
The small Indian mongoose, Urva auropunctata , is one of the most notorious invasive species in the world. In Japan, the mongoose was introduced to Amami, Kyushu (Kiire region), and Okinawa Islands. Currently, an eradication program for the Amami population is proving successful. To prevent reinvasion and conserve biodiversity, it would be advantageous to investigate the origin and dispersal history of introduced mongoose populations in Japan. We determined the mitochondrial genome of a mongoose from the Okinawa population and confirmed that the systematic status of the mongoose is Urva auropunctata . We also found two haplotypes of cytochrome b in the Amami population, one of which is common among the Okinawa, Amami, and Kiire populations. Based on our microsatellite analysis, the three populations were genetically different from each other. Furthermore, with a low pairwise F ST value, the Kiire population was closer to the Okinawa than the Amami population. Our results suggest that the Okinawa population could be the source of the Amami and Kiire populations. These results align with historical records of mongoose in Japan and clarify its genetic status. Our results should aid the prediction of the pathway through which a new invasion will likely occur.

Economic costs of protecting islands from invasive alien species - Thomas W. Bodey; Elena Angulo; Alok Bang; Céline Bellard; Jean Fantle‐Lepczyk; Bernd Lenzner; Anna Turbelin; Yuya Watari; Franck Courchamp (Conservation Biology, 2023)
Biological invasions represent a key threat to insular systems and have pronounced impacts across environments and economies. The ecological impacts have received substantial focus, but the socioeconomic impacts are poorly synthesized across spatial and temporal scales. We used the InvaCost database, the most comprehensive assessment of published economic costs of invasive species, to assess economic impacts on islands worldwide. We analyzed socioeconomic costs across differing expenditure types and examined temporal trends across islands that differ in their political geography—island nation states, overseas territories, and islands of continental countries. Over US$36 billion in total costs (including damages and management) has occurred on islands from 1965 to 2020 due to invasive species’ impacts. Nation states incurred the greatest total and management costs, and islands of continental countries incurred costs of similar magnitude, both far higher than those in overseas territories. Damage‐loss costs were significantly lower, but with qualitatively similar patterns across differing political geographies. The predominance of management spending differs from the pattern found for most countries examined and suggests important knowledge gaps in the extent of many damage‐related socioeconomic impacts. Nation states spent the greatest proportion of their gross domestic products countering these costs, at least 1 order of magnitude higher than other locations. Most costs were borne by authorities and stakeholders, demonstrating the key role of governmental and nongovernmental bodies in addressing island invasions. Temporal trends revealed cost increases across all island types, potentially reflecting efforts to tackle invasive species at larger, more socially complex scales. Nevertheless, the already high total economic costs of island invasions substantiate the role of biosecurity in reducing and preventing invasive species arrivals to reduce strains on limited financial resources and avoid threats to sustainable development goals.

Economic costs of invasive alien ants worldwide - Elena Angulo; Benjamin D. Hoffmann; Liliana Ballesteros-Mejia; Ahmed Taheri; Paride Balzani; Alok Bang; David Renault; Marion Cordonnier; Céline Bellard; Christophe Diagne; Danish A. Ahmed; Yuya Watari; et al. (Biological Invasions, 2022)
Invasive ants are amongst the most destructive and widespread invaders across the globe; they can strongly alter invaded ecosystems and are responsible for the loss of native ant species. Several studies have reported that invasive ants can also lead to substantial economic costs. In this study, we search, describe and analyse 1342 reported costs of invasive ants compiled in the InvaCost database. Economic costs, reported since 1930 for 12 ant species in 27 countries, totalled US$ 51.93 billion, from which US$ 10.95 billion were incurred, and US$ 40.98 billion were potential costs (i.e., expected or predicted costs). More than 80% of total costs were associated with only two species, Solenopsis invicta and Wasmannia auropunctata ; and two countries, the USA and Australia. Overall, damage costs amounted to 92% of the total cost, mainly impacting the agriculture, public and social welfare sectors. Management costs were primarily post-invasion management (US$ 1.79 billion), with much lower amounts dedicated to prevention (US$ 235.63 million). Besides the taxonomic bias, cost information was lacking for an average of 78% of the invaded countries. Moreover, even in countries where costs were reported, such information was available for only 56% of the invaded locations. Our synthesis suggests that the global costs of invasive ants are massive but largely biased towards developed economies, with a huge proportion of underreported costs, and thus most likely grossly underestimated. We advocate for more and improved cost reporting of invasive ants through better collaborations between managers, practitioners and researchers, a crucial basis for adequately informing future budgets and improving proactive management actions of invasive ants.

Seasonal and spatial shifts in feral cat predation on native seabirds vs. non-native rats on Mikura Island, Japan - Sarara Azumi; Yuya Watari; Nariko Oka; Tadashi Miyashita (Mammal Research, 2021)
Understanding how invasive predators impact native species is essential for the development of effective control strategies, especially in insular environments where alternative non-native prey species exist. We examined seasonal and spatial shifts in diet of feral cat Felis silvestris catus focusing on the predation on native streaked shearwaters, Calonectris leucomelas , and introduced rats, Rattus rattus and R. norvegicus , which are alternative prey to shearwaters, on Mikura Island, Japan. Streaked shearwaters breed at low elevations on the island from spring to autumn, whereas rats inhabit the island throughout the year, which makes them an alternative prey when native shearwaters are absent. Fecal analysis revealed that feral cats dramatically shifted their diets from introduced rats in winter to streaked shearwaters in seabird-season in low elevation areas of the island, while cats preyed on rats throughout the year at high altitudes on the island. This finding suggests that feral cats selectively prey on shearwaters. This is probably because of their large body size and less cautious behavior, and because introduced rats sustain the cat population when shearwaters are absent. The number of streaked shearwaters killed was estimated to be 313 individuals per cat per year, which represents an indication of top-down effects of feral cats on streaked shearwaters. Further studies on the demographic parameters and interspecific interactions of the three species are required to enable effective cat management for the conservation of streaked shearwaters on this island.

Identification of the population source of free-ranging cats threatening endemic species on Tokunoshima Island, Japan - Kazuaki Kazato; Yuya Watari; Tadashi Miyashita (Mammal Research, 2020)
Free-ranging cats Felis silvestris catus are harmful to endemic species, especially on islands. Effective management practices require an understanding of their habitat use and population source at the landscape level. We aimed to identify the source of the free-ranging cat population on Tokunoshima Island, Japan, which harbors a variety of endemic organisms as well as human settlements. Trapping data for the whole island were provided by local governments, and landscape factors (residential, agricultural, and woodlot areas and cattle barn density) affecting cat density were explored. An analysis of live-capture data indicated that the density (per 1 km 2 ) of free-ranging cats was positively correlated with the densities of cattle barns and woodlot areas and negatively correlated with residential areas. An interview survey revealed that nearly half of the cattle barns feed free-ranging cats. The source habitat of free-ranging cats appears to be areas with a high density of cattle barns and a high percentage of woodlots in human-dominated landscapes. Feeding cats in cattle barns may strengthen the bottom-up process of population growth on the island. To reduce the impact of cats on endemic species on Tokunoshima Island, efforts to stop feeding cats in cattle barns are important. Reaching a consensus with stakeholders will require further studies of the ecological risks posed by free-ranging cats.

New detection of a 30-year-old population of introduced mongoose Herpestes auropunctatus on Kyushu Island, Japan - Yuya Watari; Junco Nagata; Kimitake Funakoshi (Biological Invasions, 2011)

Effects of exotic mongoose (Herpestes javanicus) on the native fauna of Amami-Oshima Island, southern Japan, estimated by distribution patterns along the historical gradient of mongoose invasion - Yuya Watari; Seiki Takatsuki; Tadashi Miyashita (Biological Invasions, 2008)